Microglial dynamics and emerging therapeutic strategies in CNS homeostasis and pathology - Cao, Jie; Yuan, Jianqing; Liu, Nanhai; Huang, Kai; Guo, Mingwei (Frontiers in Pharmacology, 2025)
Microglia, the resident immune cells of the central nervous system (CNS), are highly dynamic and play critical roles in maintaining CNS homeostasis. Under normal conditions, microglia continuously monitor their environment, clear cellular debris, and regulate homeostasis. In response to disease or injury, however, they undergo rapid morphological and functional changes, often adopting an amoeboid shape that facilitates phagocytosis of abnormal cells, pathogens, and external antigens. Microglia also proliferate in areas of injury or pathology, contributing to immune responses and tissue remodeling. Recently, pharmacological approaches targeting microglial depletion and repopulation have gained attention as a means to reset or modulate microglial function. Techniques such as CSF1R inhibition enable transient depletion of microglia, followed by rapid repopulation, potentially restoring homeostatic functions and mitigating chronic inflammation. This review explores the current understanding of microglial dynamics and highlights emerging therapeutic applications of microglial depletion and repopulation within the CNS.